Exploring the impact of the dual-teacher teaching program on rural education under the internet + background - Wenling, Li; Muhamad, Mohd Mokhtar; Mohd Fakhruddin, Fathiyah; Zuo, Ruijia (Human Resource Management Academic Research Society, 2022)
The dual-teacher teaching model in Guangxi China is a typical case of urban-rural education support model under the Background of Internet+, in which excellent urban teachers provide high-quality teaching resources for rural schools with modern teaching technologies to promote the development of weak rural schools. To explore the effectiveness of dual-teacher teaching, this study surveyed 305 rural teachers who participated in the project. The founding showed that more than 85% of rural teachers believed the dual-teacher teaching program as "excellent", and the overall rating was high. The survey shows that the program helps promote the professional development of rural teachers, accurately helps rural teachers improve their classroom teaching, improves the learning atmosphere and academic level of rural students, and promotes the normalization of school-based training. However, there are still problems that the online resources do not match the versions of rural teaching materials, and the limited hardware conditions in rural schools affect teachers' learning and use of the project's teaching resources. Therefore, it is necessary to gain a deeper understanding of the actual needs of rural schools, maintain the integration of the demonstration resources with the local teaching reform requirements in rural areas, and suggest that the education administration should increase the support for rural schools and improve the schooling conditions in rural schools.